2022
DOI: 10.3390/ani12233429
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Quercetin against Abamectin-Induced Hemato-Biochemical Alterations and Hepatorenal Oxidative Damage in Nile Tilapia, Oreochromis niloticus

Abstract: Abamectin (ABM) is a common agricultural pesticide and veterinary anthelmintic drug. It can discharge from the sites of application to aquatic systems via surface run-off or spray drift, causing harmful effects to aquatic organisms. The present study investigated the protective effect of dietary quercetin supplementation on hemato-biochemical parameters and hepato-renal oxidative stress biomarkers in Nile tilapia (Oreochromis niloticus) exposed to a sublethal dose of ABM. Fish were allocated into six equal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…The current findings reveal that 28 days of exposure to 0.5 ug/l ABM increased levels of MDA in the brain and liver, as well as SOD, GPx, and GST in liver samples, which explains the causes of disturbance in liver and kidney functions in the ABM group in this study. The results are in line with previous research that showed that ABM can induce oxidative stress and alter the antioxidant response in several fish and shellfish species such as O. niloticus (Mahmoud et al 2021;Mansour et al 2022), Cyprinus carpio (Rohmah et al 2022, Schizothorax prenanti (Hong et al 2020a), and Eriocheir sinensis (Hong et al 2020b). Furthermore, the current research showed that dietary supplementation with MOE mitigated the adverse effects of ABM on the antioxidant system of exposed fish in ABM + MOE group.…”
Section: Discussionsupporting
confidence: 92%
“…The current findings reveal that 28 days of exposure to 0.5 ug/l ABM increased levels of MDA in the brain and liver, as well as SOD, GPx, and GST in liver samples, which explains the causes of disturbance in liver and kidney functions in the ABM group in this study. The results are in line with previous research that showed that ABM can induce oxidative stress and alter the antioxidant response in several fish and shellfish species such as O. niloticus (Mahmoud et al 2021;Mansour et al 2022), Cyprinus carpio (Rohmah et al 2022, Schizothorax prenanti (Hong et al 2020a), and Eriocheir sinensis (Hong et al 2020b). Furthermore, the current research showed that dietary supplementation with MOE mitigated the adverse effects of ABM on the antioxidant system of exposed fish in ABM + MOE group.…”
Section: Discussionsupporting
confidence: 92%
“…Plant-based phytobiotics are widely used in aquaculture as natural growth and immune boosting components (Awad and Awaad, 2017;Mohammadi et al, 2020;Al-Shawi et al, 2021;Mansour et al, 2022;Yousefi et al, 2022;Almarri et al, 2023;Mansour et al, 2023). Poten-tials of dietary parsley extract (PUE) were assayed on growth, immunity and resistance of the fish to ammonia stress.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a flavonol phytochemical, with the potential for reducing multiple stress. It is commonly known that quercetin has an ameliorative effect on a variety of environmental stresses in both plants and animals [ 7 , 8 ]. Quercetin facilitates several plant physiological processes, such as seed germination, pollen growth, antioxidant machinery, and photosynthesis, as well as inducing proper plant growth and development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%